Implementation of Anti-Corruption Education in Fostering Integrity Among Elementary School Students - Deri Ardiari Kusumah (ILAW, 2025)
This study analyzes the implementation of anti-corruption education in fostering integrity among elementary school students. The research aims to examine how anti-corruption values such as honesty, responsibility, discipline, and fairness are integrated into classroom learning and school culture. A qualitative descriptive method with a case study approach is employed, using observation, interviews, and documentation as data collection techniques. The findings indicate that anti-corruption education is effectively implemented through value integration in learning activities, teacher role modeling, and school habituation practices. Students demonstrate improved understanding and behavior when exposed to consistent and contextual value education. However, challenges remain in ensuring consistency between school-based learning and external social environments. The study concludes that sustainable and collaborative efforts between schools, teachers, and society are essential for strengthening students’ integrity through anti-corruption education.